The Decadent Counterpublic - Potolsky, Matthew (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractThis paper argues that decadent writers were highly self-conscious about their relationship to their readers, and that they regarded this relationship as a form of anti-nationalist political critique. Drawing upon Michael Warner’s notion of a “counterpublic,” the paper demonstrates the way two writers from the period—Charles Baudelaire and Aubrey Beardsely—depict and encourage the formation of cosmopolitan communities of taste in and through their accounts of the Tannhäuser legend.